2019
DOI: 10.1101/602607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ventriculo-arterial uncoupling is associated with VO2dependency in cardiac surgical patients

Abstract: Background:The clinical relevance of V-A (un)coupling in critically ill patients is under investigation. In this study we measured the association between V-A coupling and oxygen consumption (VO 2 ) response in patients with acute circulatory instability following cardiac surgery. Methods and results:Sixty-one cardio-thoracic ICU patients who received fluid challenge or norepinephrine infusion were included. Arterial pressure, cardiac output (CO), heart rate (HR), arterial (E A ), and ventricular elastances (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Therefore, increased arterial load by a high dose of NE could lead to ventricular-arterial uncoupling. However, ventricular-arterial uncoupling was reported to be associated with the oxygen consumption (VO 2 ) responsiveness to oxygen delivery (DO 2 ) increases [30], and VO 2 responsiveness was associated with high lactate [31]. Moreover, a previous study reported that restoring MAP and vascular waterfall with NE may not be systematically associated with improvement of tissue perfusion [29], and several randomized studies [32,33] did not reveal any clinical benefit with the use of a higher dose of vasopressor to maintain a higher MAP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased arterial load by a high dose of NE could lead to ventricular-arterial uncoupling. However, ventricular-arterial uncoupling was reported to be associated with the oxygen consumption (VO 2 ) responsiveness to oxygen delivery (DO 2 ) increases [30], and VO 2 responsiveness was associated with high lactate [31]. Moreover, a previous study reported that restoring MAP and vascular waterfall with NE may not be systematically associated with improvement of tissue perfusion [29], and several randomized studies [32,33] did not reveal any clinical benefit with the use of a higher dose of vasopressor to maintain a higher MAP.…”
Section: Discussionmentioning
confidence: 99%